ANALISIS KESESUAIAN ISI BUKU AJAR AL-SYĀMIL TERHADAP TUNTUTAN KELULUSAN IMKA DI UIN WALISONGO (Universitas Negeri Semarang, 2022)
Every student is required to take Arabic course organized by PPB and take the IMKA exam to measure Arabic language skills and as a prerequisite for graduation. In facing the IMKA exam, students got difficulties in solving IMKA questions. As an effort to overcome student problems, this study will analyze the suitability of the contents of al-Syāmil's textbooks to the needs of students in facing the demands of IMKA graduation. This research was conducted to answer the following problems: (1) What are the student's needs in facing the demands of IMKA graduation? (2) How is the analysis of the suitability of al-Syāmil's textbooks with the needs of students in facing the demands of IMKA graduation? This study uses a qualitative method. Data obtained from document studies, interviews and questionnaires. Data analysis was carried out in three stages, namely data reduction, data display, and drawing conclusions. The results showed that: (1) The needs of students in facing the demands of IMKA graduation were divided into three aspects, namely necessities, lacks, and wants. In the aspect of necessities and want, the needs of students are the same, while in the aspect of lacks, the needs of students are not evenly distributed (different). (2) The suitability of the al-Syāmil textbook with the needs of students is only on the aspect of necessities, while on the aspects of lacks and want, the al-Syāmil textbook is not in accordance with the needs of students in facing the demands of IMKA graduation.